Study of Old Age Security Program Development - Saragih*, Tarimantan Sanberto; Pramasanti, An Nisa; Mahaganti, Fergie Stevi; Putra, Mochammad Andika; Kara, Septa Bagas (Universitas Syiah Kuala, 2023)
This research aims to obtain an overview of the feasibility of the idea of developing the JHT Top Up Program, as a strategic solution to the problems of governance of the BPJS Ketenagakerjaan JHT Program. The object of this research is the BPJS Ketenagakerjaan Old Age Benefit Program (JHT), by Articles 35, 36, 37 and 38 of Law no. 40 of 2004 concerning the National Social Security System (UU SJSN), Law no. 24 of 2011 concerning Social Security Administering Bodies (UU BPJS), and Article 16 of Government Regulation (PP) No. 46 of 2015 concerning the Implementation of the Old Age Security Program. The quantitative method is used where primary data is collected using a questionnaire instrument. The results of this research show that the JHT Top Up Program was accepted by all segments in the survey and the success of the JHT Top Up Program in its implementation will be determined by appropriate socialization and promotion. The survey results show that the level of interest and acceptance of the JHT Top Up Program is at a moderate level (+/- 60%), on the other hand, many participants do not understand the purpose and benefits of the JHT Program (34%).